Hypoglycemic and Hypolipidemic Activities of Psychotria sylhetensis Hook in Alloxan-induced Type 2 Diabetic Rats (Bangladesh Pharmaceutical Journal, 2019)
The current study was carried out to determine the hypoglycemic and hypolipidemic activities of methanolic extract P. silhetensis leaves in alloxan-induced diabetic rats. In this study diabetes was induced in rats by intraperitoneal administration of 150 mg/kg of alloxan. Animals were treated for one week with the plant extract at doses of 250 and 500 mg/kg body weight. Metformin (100 mg/kg b.w.) was used as standard for comparison. The anti-diabetes activity was examined by measuring blood glucose level at 0, 3, 5 and 7 days in diabetic induced animal models. Blood samples were collected at day eight of the treatment and analyzed for triglyceride (TG), total cholesterol (TC), high density lipoprotein cholesterol (HDL-C) and low density lipoprotein cholesterol (LDL-C) after sacrifice. Alloxan-induced diabetic rats exhibited a significant decrease in plasma glucose level when treated with P. silhetensis leaf extract as compared to normal, diabetic control and standard rats. All tested lipid parameters were improved after the treatment with methanolic extract of P. silhetensis and metformin as compared to diabetic rats. The results of the present study showed that P. silhetensis possesses significant anti-diabetic properties and has beneficial effects on diabetic hyperlipidemia.Bangladesh Pharmaceutical Journal 22(1): 41-44, 2019